“Key Words”and Mediation Practices in Special Pedagogy - Argiropoulos, Dimitris (Psychological Counseling and Psychotherapy, 2019)
The topics of this article concern the importance of mediators in education and the inclusion of children in general and, in particular, of those children who have difficulties due to disability, disorders or handicaps. The educator must deal with the individual as a whole and, with the help of the mediators, he must be able to achieve the goals set out in his educational project (or in a relationship of support), taking into consideration the overall needs and strengths of the subject with whom he works, or rather, cooperates. The mediators are defined as a relational resource and as a support to therapeutic, educational and assistance initiatives. They could act as harmonizers and attenuators in particular conditions of stress, suffering and conflict and they could be a valid aid for people with various problems in relationships, communication and with disturbed social behavior. Especially they would support minors, but also those people who have difficulties due to disability, including intellectual disability, and those people who are living critical situations of personal and social vulnerability or suffer an extreme social marginalization. This article highlights the particular importance of mediations and mediators in educational-pedagogical practices in schools and extra-scholastic settings, which are necessary for the growth and learning of children with disabilities. These children must be guaranteed the right to have a complete education in an “ordinary” and not separate, that is inclusive, social path.